Dutch Atlantic Connections, 1680-1800 : Linking Empires, Bridging Borders - Roitman, J.V (Atlantic World, 2014)
This title is available online in its entirety in Open Access. Dutch Atlantic Connections reevaluates the role of the Dutch in the Atlantic between 1680-1800. It shows how pivotal the Dutch were for the functioning of the Atlantic sytem by highlighting both economic and cultural contributions to the Atlantic world.